Wanneer jongmense hoop verloor: 'n pastorale perspektief op die selfmoordkontemplerende adolessent - A. R. Brunsdon; J. Janse van Rensburg (Acta Theologica, 2003)
Suicide among adolescents is escalating in Western societies. It is surmised that the development towards adolescence as well as the fast-changing living environment of adolescents in South Africa are conducive to the hopelessness and despair among young people contemplating suicide. As suicide manifests itself over time, this phenomenon should, however, leave room for therapeutic intervention. Pastoral therapy has access to Biblical paradigms, which are highly reconcilable with hopelessness and despair. A covenant-driven pastoral approach could serve as an example of the contribution which pastoral therapy could make towards combating this destructive phenomenon.